A novel PINK1- and PARK2-dependent protective neuroimmune pathway in lethal sepsis. Issue 12 (1st December 2016) - Kang, Rui; Zeng, Ling; Xie, Yangchun; Yan, Zhengwen; Zhou, Borong; Cao, Lizhi; Klionsky, Daniel J.; Tracey, Kevin J.; Li, Jianhua; Wang, Haichao; Billiar, Timothy R.; Jiang, Jianxin; et al.
ABSTRACT: Although the PINK1-PARK2 pathway contributes to the pathogenesis of Parkinson disease, its roles in sepsis (a major challenge for critical care) were previously unknown. Here, we show that pink1 −/− and park2 −/− mice are more sensitive to polymicrobial sepsis-induced multiple organ failure and death. The decrease in the circulating level of the neurotransmitter dopamine in pink1 −/− and park2 −/− mice accelerates the release of a late sepsis mediator, HMGB1, via HIF1A-dependent anaerobic glycolysis and subsequent NLRP3-dependent inflammasome activation. Genetic depletion of Nlrp3 or Hif1a in pink1 −/− and park2 −/− mice confers protection against lethal polymicrobial sepsis. Moreover, pharmacological administration of dopamine agonist (e.g., pramipexole), HMGB1-inhibitor (e.g., neutralizing antibody or glycyrrhizin), or NLRP3-inhibitor (e.g., MCC950) reduces septic death in pink1 −/− and park2 −/− mice. The mRNA expression of HIF1A and NLRP3 is upregulated, whereas the mRNA expression of PINK1 and PARK2 is downregulated in peripheral blood mononuclear cells of patients with sepsis. Thus, an impaired PINK1-PARK2-mediated neuroimmunology pathway contributes to septic death and may represent a novel therapeutic target in critical care medicine.